Soil fungal community succession regulates aggregate C sequestration and organic C pool stability following reclamation of Chinese estuarine wetlands - Zhenteng Li; Weiqi Wang; Shaoying Lin; Jordi Sardans; Junma Chen; Xiaoying Ren (Environmental Research, 2026)

Projected runoff responses to climate and vegetation changes on the Tibetan Plateau - Bo Feng; Xianhong Meng; Xianyu Yang; Mingshan Deng; Lin Zhao; Zhaoguo Li; Shaoying Wang (Atmospheric Research, 2026)

Extreme precipitation during the warm growing season amplifies methane emissions and reduces non-growing season contributions in a Tibetan alpine peatland - Zhenrong Lin; Zhirang Wu; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; Shaoying Wang; Xianhong Meng; Ruijun Long; Lei Ma (Agricultural and Forest Meteorology, 2026)

Heterologous Expression of Liriodendron sino-americanum LhWUS Promotes Branching in Arabidopsis thaliana - Tangrui Zhao; Shaoying Wen; Jun Yang; Junhong Lin; Huogen Li (Journal of Plant Growth Regulation, 2026)

Microbially driven iron redox cycling dominates Fe-bound organic carbon formation in coastal wetlands under sea level rise - Zhuang Huang; Shaoying Lin; Chun Wang; Jordi Sardans; Ning Hou; Yangyang Xie; Weiqi Wang; Josep Peñuelas; Ming Jiang (Water Research, 2026)

Molecular phylogeny and taxonomy of Mus pahari (Rodentia: Muridae) - Qingfang Zou; Lin Gu; Tao Zhang; Chengxin Zhou; Xuming Wang; Tong Zhang; Keji Guo; Shaoying Liu; Shunde Chen (Mammalian Biology, 2026)

From gene to function: GABA receptor-associated protein (GABARAP) interacts with and potentiates the GABA receptor (RDL) in Megalurothrips usitatus (Bagnall) (Thysanoptera: Thripidae) - Haifeng Jin; Yonghui Lin; Sumit Singh; Yuran Xie; Wayne Jiang; Fen Li; Shaoying Wu (Pesticide Biochemistry and Physiology, 2026)

Manure-driven antibiotic resistance in agroecosystems: Decadal evidence of accumulation dynamics and food chain transmission - Shuang Peng; Shaoying Xu; Beibei Zhou; Qingqing Hua; Pan Wu; Xiangui Lin; Yiming Wang (Journal of Hazardous Materials, 2026)

Fe/Mn/Zr ternary electrode facilitates ultra-low-resistance electrocatalysis for closed-loop electrochemical removal of heavy metals from industrial wastewater - Shaoying Lin; Xinyu Liu; Huiqiang Ma; Yanzhuang Liu; Yameng Wang; Haoran Liu; Bo Wang; Yihua Li; Changfei Gao (Chemical Engineering Journal, 2025)

Fine-scale poverty estimation by integrating SDGSAT-1 glimmer images and urban functional zoning data - Zejia Chen; Huishan Luo; Minting Li; Jinyao Lin; Xinchang Zhang; Shaoying Li (Remote Sensing of Environment, 2025)

Physical protection by soil aggregates drives carbon gains in mangrove restoration: Evidence from coastal aquaculture ponds - Ning Hou; Xiaolei Yin; Weiqi Wang; Xiang Yang; Yuan Li; Yuanchun Zou; Zhaoliang Song; Shaoying Lin; Zhineng Xiao; Rongbin Yin; Fanjiang Zeng; Zhihao Zhang; et al. (Journal of Environmental Management, 2025)

Polyvinylpyrrolidone-modified Ce Al bimetallic oxide loaded on recyclable activated carbon for selective fluoride ion removal from aqueous solutions - Fuwang Zheng; Shaoying Guo; Junchao Xu; Juan Jiang; Chunshan Wu; Qiyuan Sun; Yuyi Zheng; Yilong Lin (Journal of Water Process Engineering, 2025)

National-scale connectivity analysis and construction of forest networks based on graph theory: A case study of China - Jinyao Lin; Yu Wang; Zhuochun Lin; Shaoying Li (Ecological Engineering, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Assessing the influence of green space morphological spatial pattern on urban waterlogging: A case study of a highly-urbanized city - Wenli Zhang; Suixuan Qiu; Zhuochun Lin; Zhixin Chen; Yuchen Yang; Jinyao Lin; Shaoying Li (Environmental Research, 2025)

Nonlinear and threshold effects of urban building form on carbon emissions - Yuqin Huang; Shaoying Li; Jinyao Lin; Lixuan Zheng; Caigang Zhuang; Chutong Guan; Yanzhen Guo; Yaye Zhuang (Energy and Buildings, 2025)

Fertilizer reduction and biochar amendment promote soil mineral-associated organic carbon, bacterial activity, and enzyme activity in a jasmine garden in southeast China - Fajun Yang; Weiqi Wang; Ziwei Wu; Jiahao Peng; Hongda Xu; Maoquan Ge; Shaoying Lin; Yu Zeng; Jordi Sardans; Chun Wang; Josep Peñuelas (Science of The Total Environment, 2024)

Observed surface heat fluxes partitioning during the local growing season over the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Danrui Sheng; Hanlin Niu; Peili Wu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Shaoying Wang; Shihua Lyu (Agricultural and Forest Meteorology, 2024)

Spatiotemporal Variability and Environmental Controls of Temperature Sensitivity of Ecosystem Respiration across the Tibetan Plateau - Danrui Sheng; Xianhong Meng; Shaoying Wang; Zhaoguo Li; Lunyu Shang; Hao Chen; Lin Zhao; Mingshan Deng; Hanlin Niu; Pengfei Xu; Xiaohu Wen (Advances in Atmospheric Sciences, 2024)

Losses and destabilization of soil organic carbon stocks in coastal wetlands converted into aquaculture ponds - Shaoying Lin; Yaxin Zhou; Weiqi Wang; Jordi Sardans; Yuan Li; Chuancheng Fu; Fanjiang Zeng; Zhaoliang Song; Akash Tariq; Josep Peñuelas (Global Change Biology, 2024)
Coastal‐wetlands play a crucial role as carbon (C) reservoirs on Earth due to their C pool composition and functional sink, making them significant for mitigating global climate change. However, due to the development and utilization of wetland resources, many wetlands have been transformed into other land‐use types. The current study focuses on the alterations in soil organic‐C (SOC) in coastal‐wetlands following reclamation into aquaculture ponds. We conducted sampling at 11 different coastal‐wetlands along the tropical to temperate regions of the China coast. Each site included two community types, one with solely native species ( Suaeda salsa , Phragmites australis and Mangroves) and the other with an adjacent reclaimed aquaculture pond. Across these 11 locations we compared SOC stock, active OC fractions, and soil physicochemical properties between coastal wetlands and aquaculture ponds. We observed that different soil uses, sampling sites, and their interaction had significant effects on SOC and its stock ( p p p

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Enhanced lanthanum and cerium removal of self-powered electro-membrane bioreactor (SPEMBR) using high-active bi-functional M-N-CNTs@Fe/Mo electrode - Hui Lu; Hongbo Wang; Changfei Gao; Lifen Liu; Tingting Yu; Yihua Li; Shaoying Lin (Chemical Engineering Journal, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

A novel index for assessing the rural population hollowing at fine spatial resolutions based on Tencent social media big data: A case study in Guangdong Province, China - Fang Wang; Shaoying Li; Lin Liu; Feng Gao; Yanfen Feng; Zilong Chen (Land Use Policy, 2024)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Evaluation of surface albedo over the Tibetan Plateau simulated by CMIP5 models using in‐situ measurements and MODIS - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Shaoying Wang; Lunyu Shang; Hao Chen; Shihua Lyu (International Journal of Climatology, 2022)
Surface albedo plays a key role in the energy and water cycles, and reasonable parameterizations of surface albedo will be greatly helpful to improve the simulation of radiation partition in climate models. In‐situ measurements of albedo from five sites over the Tibetan Plateau (TP) and MODIS albedo product are used to evaluate monthly, annual, and seasonal variations of the surface albedo simulated by 24 Global Climate Models (GCMs) archived by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Potential factors contributing to the bias of simulated albedo were investigated. The results show that the monthly albedo of 24 GCMs varied across models, and the difference among the models was smaller in the June–July–August period than the December–January–February period. The ensemble mean albedo of the 24 GCMs was more consistent with the in‐situ measurements than the individual model. The albedo calculated from the BNU‐ESM, GFDL‐CM3, INM‐CM4, MIROC4h, MIROC‐ESM, and MIROC‐ESM‐CHEM models coincided with the observations from June to September, increasing rapidly to above 0.4 from November. However, the annual cycle of surface albedo was insignificant when simulated by some models, such as CanESM2, CSIRO‐Mk3.6.0, CMCC‐CMS, IPSL‐CM5A‐MR, and MPI‐ESM‐MR. Additionally, the surface albedo was overestimated by CMIP5 multi‐model ensemble mean—with a smaller amplitude of daily albedo—compared with the values estimated from in‐situ observations and MCD43A3. In all 24 models, snow albedo parameterization schemes were found to variably fit the attenuation of snow albedo over time. The cold temperature, relatively more precipitation, fresh snow density, and albedo in these models led to large biases in snow depth and ablation. The surface albedo tends to increase without the influence of blowing snow and withered grass on the model's albedo.

Muscovy Duck Reovirus Infection Disrupts the Composition of Intestinal Microbiota in Muscovy Ducklings - Xiuqin Chen; Min Zheng; Meiqing Huang; Shifeng Xiao; Fengqiang Lin; Shaoying Chen; Shilong Chen (Current Microbiology, 2020)

Downregulation of LncRNA GAS5 promotes liver cancer proliferation and drug resistance by decreasing PTEN expression - Congren Wang; Shaoying Ke; Mingzhu Li; Conglin Lin; Xiaoyu Liu; Qunxiong Pan (Molecular Genetics and Genomics, 2020)

Isolation and characterization of a distinct duck-origin goose parvovirus causing an outbreak of duckling short beak and dwarfism syndrome in China - Shilong Chen; Shao Wang; Xiaoxia Cheng; Shifeng Xiao; Xiaoli Zhu; Fengqiang Lin; Nanyang Wu; Jinxiang Wang; Meiqing Huang; Min Zheng; Shaoying Chen; Fusong Yu (Archives of Virology, 2016)

Turbulent transfer coefficient and roughness length in a high-altitude lake, Tibetan Plateau - Zhaoguo Li; Shihua Lyu; Lin Zhao; Lijuan Wen; Yinhuan Ao; Shaoying Wang (Theoretical and Applied Climatology, 2016)

Elemental sulfur in northern South China Sea sediments and its significance - Qi Lin; JiaSheng Wang; ShaoYing Fu; HongFeng Lu; QingTao Bu; RongXiao Lin; Fei Sun (Science China Earth Sciences, 2015)

Evidence for natural recombination in the capsid gene VP2 of Taiwanese goose parvovirus - Shao Wang; Xiaoxia Cheng; Shaoying Chen; Fengqiang Lin; Shilong Chen; Xiaoli Zhu; Jingxiang Wang (Archives of Virology, 2015)

Isolation and characterization of a Chinese strain of Tembusu virus from Hy-Line Brown layers with acute egg-drop syndrome in Fujian, China - Shilong Chen; Shao Wang; Zhaolong Li; Fengqiang Lin; Xiaoxia Cheng; Xiaoli Zhu; Jingxiang Wang; Shaoying Chen; Meiqing Huang; Min Zheng (Archives of Virology, 2014)

The crustal structures of the central Longmenshan along and its margins as related to the seismotectonics of the 2008 Wenchuan Earthquake - ShiXu Jia; BaoJin Liu; ZhaoFan Xu; Zhi Liu; ShaoYing Feng; JianShi Zhang; JieYan Lin; XiaoFeng Tian; QiaoXia Liu; WenBin Guo (Science China Earth Sciences, 2014)

Reverse transcription loop-mediated isothermal amplification for rapid detection of the newly emerged poultry Flavivirus - Zhaolong Li; Shaoying Chen; Shao Wang; Shilong Chen; Fengqian Lin (Folia Microbiologica, 2013)